Symbolization of Educational Messages on the Cianjuran Sundanese Song: A Study of the Structure and Meaning of Lyrics - Sukanta , Sukanta; Supiarza, Hery; Sarbeni, Irwan (Bina Nusantara University, 2023)
The research discussed Tembang Sunda Cianjuran (Cianjuran Sundanese Song) which contained a very high quality of music and was full of hidden wisdom values as a reflection of the people who created it. In a cross-generational context, transforming wisdom values was considered an educational process. The research used an anthropological approach to uncover the mystery behind the song’s structure and lyrics’ meaning and structuralism theory to interpret the meaning behind the structure. Data collection techniques were carried out by interviewing and studying archives of old documents in the form of audio recordings related to the Tembang Sunda Cianjuran, especially the genre of Papantunan (poetry-like). The collected data were identified, classified, then interpreted, and compiled qualitatively. The results illustrate that educational messages communicated through the lyrics of Papantunan as well as the process of transforming the values of past Sundanese’ lives into symbols, are carried out across generations. The substance of the values contained includes catur watak (four characters), which consists of education about courage (leber wawanen), faithful to promises (kukuh kana jangji), prioritizing the glory of life (medang kamulyan), and silih asih (giving each other the affection), silih asah (honing each other in intelligence or skills), and silih asuh (caring each other). All of this is packaged in the form of a pupuh poem and sung by a juru tembang accompanied by kacapi suling.